1986
DOI: 10.3109/13816818609004133
|View full text |Cite
|
Sign up to set email alerts
|

Optic atrophy in Wolfram syndrome

Abstract: The clinical and electrophysiologic findings in 11 cases of Wolfram syndrome are presented. These findings suggest that optic atrophy in Wolfram syndrome is not secondary to retinal pathology, but probably represents part of a generalized degeneration of neural structures. The relationship of diabetes mellitus to this process of neural degeneration remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Our Cisd2 gene knockout mouse work provides strong evidence supporting the hypothesis that WFS is a mitochondria-mediated disorder; thus, specifically, WFS2, which is caused by a CISD2 mutation, is a mitochondria-mediated disorder. Previous clinical studies in WFS patients suggested that optic atrophy probably represents a degeneration of the optic nerve (Mtanda et al 1986;. Indeed, our mouse work has revealed that progressive degeneration of the optic nerve is one of the earliest phenotypic features detected at 2-3 wk of age, which is before weaning; this phenotype exacerbates with age in the Cisd2 À/À offspring ( Fig.…”
Section: Wfs2 Is a Mitochondria-mediated Disordermentioning
confidence: 73%
“…Our Cisd2 gene knockout mouse work provides strong evidence supporting the hypothesis that WFS is a mitochondria-mediated disorder; thus, specifically, WFS2, which is caused by a CISD2 mutation, is a mitochondria-mediated disorder. Previous clinical studies in WFS patients suggested that optic atrophy probably represents a degeneration of the optic nerve (Mtanda et al 1986;. Indeed, our mouse work has revealed that progressive degeneration of the optic nerve is one of the earliest phenotypic features detected at 2-3 wk of age, which is before weaning; this phenotype exacerbates with age in the Cisd2 À/À offspring ( Fig.…”
Section: Wfs2 Is a Mitochondria-mediated Disordermentioning
confidence: 73%
“…The age of onset and clinical features of the Wolfram syndrome patients are shown in table 1; some of these have been described previously [van den Ouweland, 2003;Mtanda et al, 1986]. Figure 2 shows the audiometric data (single and serial observations) obtained for all patients with Wolfram syndrome and their non-affected heterozygous relatives (carriers) with one WFS1 mutation, arranged by family.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, Wfs1 is probably distributed as an ER membrane protein in the inner segments and cell bodies of photoreceptors (Takeda et al, 2001;Hofmann et al, 2003), and is considered responsible for the maintenance of phototransduction. In addition, slight photoreceptor dysfunction is suspected in Wolfram syndrome patients (Yamamoto et al, 2006), since the subjective dark adaptation curve in Wolfram syndrome patients shows a diminution of both cone and rod adaptation (Mtanda et al, 1986).…”
Section: The Journal Of Comparative Neurologymentioning
confidence: 99%
“…The ophthalmologic signs are a progressive decrease in visual acuity, constriction of the peripheral visual field with or without central scotoma, color vision disturbance, and bilateral optic disc atrophy. Diabetic retinopathy is a rare complication (Mtanda et al, 1986;Seynaeve et al, 1994;Barrett et al, 1997). Although a profound reduction in visual function is observed in Wolfram syndrome patients, the electroretinogram (ERG) tests indicate normal or only slightly reduced responses (Niemeyer and Marquardt, 1972;Mtanda et al, 1986;Seynaeve et al, 1994;Barrett et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation